Mindfulness and compassion training for health professionals: A qualitative study - Brun, Clémence; Akinyemi, Alexis; Houtin, Laurène; Mizzi, Claire; Cardoso, Thierry; Isnard Bagnis, Corinne (Frontiers in Psychology, 2023)
Background: Compassion is a key component of quality care. Encouraging Health Care Professionals (HCPs) to develop a patient-centered care relationship through mindfulness and compassion training may be beneficial for both patients and HCPs. Method: We assessed the impact of a compassion-centered mindfulness program (i.e., the Mindfulness Based (MB) CARE program) on healthcare practice conducting 10 phone interviews with HCPs who experienced the program. Results: The training had an overall positive impact on the HCPs ability to feel compassion toward their patients and themselves, helped them develop kindness towards themselves and their patients, and enhanced their attention to their patient’s needs and theirs. Participants were better able to accept the difficult work experiences or those their patients experienced, with more perceived equanimity and less reactivity. Conclusions: Professional mindfulness and compassion training programs could be operational levers for institutions aiming at fostering more compassionate HCPs–patients relationships.